Please answer this question correctly and become rice.
Attachments:
![](https://hi-static.z-dn.net/files/de8/1c8ebbf966944824e23dbd97d57b0dc3.jpg)
Answers
Answered by
1
15)
Let M (proportional to) Vadbgc
Now Hence M = k Vadbgc where k is constant of proportionality
[M] = [V]a[d]b[g]c
M1L0T0 = (L1T-1)a(M1L-3)b(L1T-2)c
M1L0T0 = Mb La - 3b + c T-a - 2c
Comparing the powers,
b = 1
a - 3b + c = 0
Hence,
a - 3(1) + c = 0
a + c = 3 ...........1
-a - 2c = 0 ............2
Solving equations 1 and 2,
a + c = 3
-a - 2c = 0
---------------
-c = 3
Hence, c = - 3.
Substituting c = -3 in equation 1, we get a = 6.
Thus, M = k V6dg
hence, it can be said that M varies with 6th power of velocity
hope this ans help you ..
Similar questions
Social Sciences,
7 months ago
Math,
7 months ago
Social Sciences,
7 months ago
Science,
1 year ago
Math,
1 year ago
Math,
1 year ago